2016
DOI: 10.1016/j.ultrasmedbio.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Rheological Properties of Contrast Microbubble Targestar P as a Function of Ambient Pressure

Abstract: In this Technical Note, we determine the interfacial rheological parameters of the encapsulation of the contrast agent Targestar P using ultrasound attenuation. The characteristic parameters are obtained according to two interfacial rheological models. The properties-surface dilatational elasticity (0.09 ± 0.01 N/m) and surface dilatational viscosity (8 ± 0.1E-9 N·s/m)-are found to be of similar magnitude for both models. Contrast microbubbles experience different ambient pressure in different organs. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…48,49 Furthermore, motivated by in-vivo blood pressure variations, Kumar et al measured shell properties at overpressures up to 200 mm Hg (27 kPa). 50 For Definity bubbles with a very similar shell composition to the 10% PEG lipid mixture used here, Kumar et al 51 also found a shell viscosity and shell elasticity increase for increased ambient pressures.…”
Section: Resultsmentioning
confidence: 57%
“…48,49 Furthermore, motivated by in-vivo blood pressure variations, Kumar et al measured shell properties at overpressures up to 200 mm Hg (27 kPa). 50 For Definity bubbles with a very similar shell composition to the 10% PEG lipid mixture used here, Kumar et al 51 also found a shell viscosity and shell elasticity increase for increased ambient pressures.…”
Section: Resultsmentioning
confidence: 57%
“…We have shown that different models of coating often give rise to qualitatively similar behaviours (Kumar & Sarkar 2015; Xia et al. 2015; Kumar & Sarkar 2016) even for nonlinear response. We expect that they would vary very little in their predictions of linear dynamics.…”
Section: Mathematical Formulationmentioning
confidence: 82%
“…where We s b = ρR 3 0 ω 2 /E s 0 , Re s b = ρR 3 0 ω/κ s , γ 0 /E s 0 and α s are the non-dimensional numbers related to the coating parameters. We have shown that different models of coating often give rise to qualitatively similar behaviours (Kumar & Sarkar 2015;Xia et al 2015;Kumar & Sarkar 2016) even for nonlinear response. We expect that they would vary very little in their predictions of linear dynamics.…”
Section: Effects Of the Shell On A Contrast Microbubblementioning
confidence: 83%
See 2 more Smart Citations